Is the Correct Anatomical Placement of the Electrocardiogram (ECG) Electrodes Essential to Diagnosis in the Clinical Setting: A Systematic Review - Hadjiantoni, Alexandros; Oak, Katy; Mengi, Siddhartha; Konya, Judit; Ungvari, Tamas (Cardiology and Cardiovascular Medicine, 2021)
Background: Anatomical misplacement of the Electrocardiogram (ECG) electrode(s) is common, with significant impact on clinical diagnosis. Reasons are multi-faceted, with this review examining the consequential effects of misplacement to ECG morphology, diagnosis, prognosis, patient outcomes, and potential impact to patient care pathway. Objectives: This review examined the significance of misplacement, its’ commonality and ensuing effect on patient safety, accurate ECG acquisition and diagnosis, with evaluation of reasons for such misplacement. Methodology: Review of available literature was conducted using electronic databases. In-line with the Preferred Reporting Items for Systematic reviews and Meta – analysis protocols (PRISMA) 2015 checklist, this review was conducted with search criteria, search terms, eligibility for inclusion/ exclusion criteria, extraction and data analysis predetermined by the authors. Keywords were arranged according to grouping of terms surrounding ECG, anatomical placement, and diagnosis. The search strategy was conducted during September/October 2019. Scoping searches were conducted alongside reference lists of included studies hand searched (Snowballing) for further relevant studies. The Critical Appraisal Skills Programme (CASP) was used to methodically appraise papers (CASP, 2019). Screening of titles and abstracts of identified citations was performed by a single reviewer. Eligible articles then full text screened independently by two reviewers. Disagreements were discussed and resolved by a third reviewer. In instances of unclear reporting, authors were contacted to provide further information and clarity. Assessment of relevant literature and critical appraisal of primary research, pertaining to the clinical diagnosis and effects of anatomical misplacement of ECG electrodes, formulate the thematic discussion drawn by t